Studi Fenomenologi: Pengalaman Psikologis Perempuan Pasca Histerektomi : Literatur Riview - Ibnu Fauzi; Sri Wahyuni; Herry Susanto (Jurnal Ners, 2026)
Background: Hysterectomy is a surgical procedure involving the removal of the uterus, which may affect both the physical and psychological condition of women. The loss of the uterus is often associated with diminished femininity, decreased self-esteem, negative body image, and psychosexual disorders. In addition, social factors such as spousal support play a significant role in women’s psychological adaptation after hysterectomy. Objective: This literature review aims to analyze the psychological, sexual, and quality of life impacts experienced by women after hysterectomy, as well as the factors influencing their adaptation. Methods: This study employed a literature review method. Articles were retrieved from national and international databases such as PubMed, ScienceDirect, EBSCO, and Google Scholar. Keywords used included psychological issues after hysterectomy, body image, self-esteem, sexual function, and quality of life. Eligible articles were full-text national and international publications from the last eight years, screened for relevance to topic, research methods, and study results. Results: Hysterectomy may lead to depression, anxiety, negative body image, low self-esteem, and sexual dysfunction. However, spousal support, education, and psychological interventions have been shown to improve self-acceptance, confidence, and women’s quality of life. Conclusion: Hysterectomy has complex psychological impacts on women, ranging from depression, anxiety, and negative body image to sexual dysfunction. Spousal support, education, and psychological interventions are crucial to enhancing self-acceptance, quality of life, and overall well-being of women after hysterectomy. .